Responsabilidad social universitaria y estrategias comunicacionales - Suazo Suárez, Luis Esteban (2021)
The study performs an analysis of the communication strategies used by the Universidad International del Ecuador and Universidad de las Arts del Ecuador, in the development and fulfillment of University Social Responsibility during 2019. The study has a mixed approach, in which various qualitative and quantitative methods and techniques were used. Surveys were applied to students and interviews to teachers, in the same way, a chronological analysis of the behavior of social networks was carried out, of the two universities studied, specifically of the social network Facebook and of web pages, according to criteria such as type of uploaded content, frequency, etc...........